Soy isoflavone-caused shunting of the corticosteroidogenesis pathways in andropausal subjects: Top-down impulse for the optimal supplementation design - Ajdžanović, Vladimir; Miler, Marko; Šošić-Jurjević, Branka; Filipović, Branko; Milenkovic, Dragan; Jakovljević, Vladimir; Milošević, Verica (Medical hypotheses, 2021)
In a series of our previous works, we revealed the beneficial effects of applied soy isoflavones (genistein or daidzein) on the wide context of corticosteroidogenesis in vivo, in a rat model of the andropause. Soy isoflavones decreased the circulating levels of pituitary adrenocorticotropic hormone, inhibited aldosterone secretion, as well as corticosterone production and secretion, but stimulated dehydroepiandrosterone secretion, all in andropausal rats. In vitro studies indicate that the mechanism underlying these hormonal changes relies on inhibition of the pituitary tyrosine kinase and adrenocortical 3β-hydroxysteroid dehydrogenase enzymes by soy isoflavones. Although the clinical studies are in their infancy, the opinion is that genistein and daidzein have therapeutic potential for the safe treatment of ageing-caused androgen deprivation and glucocorticoid excess with related metabolic/hemodynamic issues in males. Our accumulated experience and knowledge in the field of biomedical effects of plant polyphenols have provided a platform for potential recommending the agenda to organize and accelerate experimental research aimed at producing the optimal supplementation. We hypothesize that an in vivo approach should first be exploited in the sequence of investigative steps, followed by in vitro studies and synchronously conducted molecular docking analyses. In vivo research, besides establishing the margin of exposure safety or adjustment of the correct polyphenol dose, enables identification and quantification of the metabolites of applied polyphenols in the blood. Subsequent in vitro exploitation of the metabolites and related docking analyses provide clarification of the molecular mechanisms of action of applied polyphenols. Chemical modification of the polyphenol structure or coupling it with nanoparticles might be the next step in optimizing the design of supplementation. Selected, intact or chemically-modified polyphenol molecules should be included in preclinical studies on a more closely-related species, while clinical studies would finally assess the safety and effectiveness of a polyphenol-based remedial strategy. The final supplement represents a product of an appropriate technological process, conducted in accordance with the recommendations derived from the preceding research.